PENINGKATAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK MATERI GAYA MELALUI MODEL TEAMS GAMES TOURNAMENT - Lestari, Vivin Ayu; Syafi’aturrosyidah, Mustika; Maghfiroh, Lailatul (MIDA : Jurnal Pendidikan Dasar Islam, 2024)
The background of this research is because of the difficulties experienced by the fourth grade students of MI Al-Mukhlisin in understanding thematic subjects of science content. This is evidenced by the passive activity of students and low student learning outcomes. The reason is that the implementation of the learning process is conventional and less varied. The formulation of the problem from this research, namely: (1) how is the application of the TGT model in increasing learning activities and outcomes, (2) whether the TGT model can increase student activity and learning outcomes in thematic learning of science content in class IV MI Al-Mukhlisin style material?. This research uses classroom action research. The subjects of this study were students of class IV A MI Al-Mukhlisin with a total of 24 students. From the research results, it can be seen that (1) the application of the TGT model is carried out through class presentations, group learning, games, tournaments, and awards. (2) in the application of the TGT model there is an increase in student activity and learning outcomes in each cycle. It is proven by the overall activity of the students in the first cycle reaching a percentage of 75%, while the second cycle increased by 84%. The student learning outcomes in the first cycle obtained the percentage of completeness reaching 67%, while the second cycle experienced an increase in the percentage of completeness by 87.5%. Thus, the Teams Games Tournament model can increase student activity and learning outcomes in thematic learning of science content for class IV MI AL-Mukhlisin style material.